Profil Tingkat Penalaran Ilmiah Siswa Sekolah Menengah Atas Pada Materi Ekosistem: (Profile Of The Level Of Scientific Reasoning Of High School Student On Ecosystem Material) - Gina Aulia Handayani; Sistiana Windyariani; Rizqi Yanuar Pauzi (Program Studi Pendidikan Biologi FKIP Universitas Jambi, 2020)
Scientific Reasoning is the systematic and logical thinking skills for problem solving. The purpose of this preliminary study is to find out the scientific reasoning profile of students in grade XI of Sukabumi City Public High School on Ecosystem material which was conducted in February in the 3rd week in one of the Sukabumi City State High Schools. This research uses descriptive method, the approach used is quantitative approach. Samples were taken using a purposive sampling technique of 30 students. This research instrument was in the form of a scientific reasoning test developed by Lawson namely the LCTSR (Lawson Classroom Test of Scientific Reasoning) type. The questions used consist of 35 multiple choice questions with LCTSR type with 6 indicators of scientific reasoning namely proportional, probabilistic, correlational, identification and control of variables, volume conservation and hypothetic-deductive. Data analysis with scoring technique is done in pairs which gives a description of the pattern and level of students' scientific reasoning abilities. From the results of the study showed that the scientific reasoning profile of class XI State Senior High School students in Sukabumi City in 2019/2020 had the highest reasoning pattern in the transitional operational category of 76.7% and had a level of scientific reasoning in the less-than-average category. average percentage of 30.05%. But these results must still be improved again by using methods, models and learning approaches that are able to train students' scientific reasoning.